2021
DOI: 10.3390/ijerph18083863
|View full text |Cite
|
Sign up to set email alerts
|

Unhealthy Food and Psychological Stress: The Association between Ultra-Processed Food Consumption and Perceived Stress in Working-Class Young Adults

Abstract: Background: Ultra-processed foods are industrial formulations made from food extracts or constituents with little or no intact food and often containing additives that confer hyper-palatability. The consumption of these products increases the risk of chronic non-communicable diseases. Stressed people may engage in unhealthy eating as a way to cope. This study aimed to verify whether ultra-processed food consumption was associated with perceived stress levels in industrial and retail workers from Vitoria da Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Although the third study reported a beta-coefficient, it was not possible to estimate the confidence interval given an exact p-value or measure of variance were not reported [17]. Similarly, four studies [20,[25][26][27] did not report p-values. We estimated these by using the confidence intervals as per the methods proposed by [47].…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Although the third study reported a beta-coefficient, it was not possible to estimate the confidence interval given an exact p-value or measure of variance were not reported [17]. Similarly, four studies [20,[25][26][27] did not report p-values. We estimated these by using the confidence intervals as per the methods proposed by [47].…”
Section: Discussionmentioning
confidence: 97%
“…Eleven studies modelled ultra-processed food consumption as the exposure variable and mental disorder parameters as the outcome [17][18][19]21,[23][24][25][26]30,48,50], with the remaining six modelling associations in the opposite direction [20,22,[27][28][29]31].…”
Section: Details Of Exposure Variables and Average Ultra-processed Fo...mentioning
confidence: 99%
See 3 more Smart Citations